2019
DOI: 10.1536/ihj.18-339
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transcatheter Aortic Valve Implantation in Patients with Cirrhosis

Abstract: Cirrhosis is a significant adverse factor of cardiac surgeries. Transcatheter aortic valve implantation (TAVI) has evolved as a less invasive therapy for aortic stenosis, whereas detailed case analysis of TAVI in cirrhotic patients is limited.Among 444 consecutive patients who underwent TAVI in the Sakakibara Heart Institute between October 2013 and January 2018, we retrospectively reviewed 11 patients (2.5%) with cirrhosis. All outcomes were defined according to the Valve Academic Research Consortium-2 criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…As seen in prior studies, patients with ESLD and ESRD had longer preprocedural and postprocedural length of stay due to careful management of comorbidities preprocedure and postprocedure. 14,21 Despite longer lengths of stay, patients with ESLD and ESRD did not have higher rates of cerebrovascular events, pacemaker placement, or vascular complications. The relatively younger age of the ESLD and ESRD cohort may mean lower burden of calcific disease and, therefore, low rates of conduction abnormalities, atherosclerotic emboli, and vascular events.…”
Section: Echocardiographic Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…As seen in prior studies, patients with ESLD and ESRD had longer preprocedural and postprocedural length of stay due to careful management of comorbidities preprocedure and postprocedure. 14,21 Despite longer lengths of stay, patients with ESLD and ESRD did not have higher rates of cerebrovascular events, pacemaker placement, or vascular complications. The relatively younger age of the ESLD and ESRD cohort may mean lower burden of calcific disease and, therefore, low rates of conduction abnormalities, atherosclerotic emboli, and vascular events.…”
Section: Echocardiographic Findingsmentioning
confidence: 98%
“…In patients with ESLD and ESRD, TAVR has emerged as a potential alternative to surgery, 1,6-8,13,19-21 however, there remains few studies evaluating clinical and echocardiographic outcomes after TAVR in patients pretransplant with ESLD and ESRD. [12][13][14] Though TAVR is an appealing alternative for high risk surgical patients, [19][20][21][22] cirrhosis who underwent TAVR demonstrated in-hospital mortality rates between 9 and 36%, and 1 year mortality rates between 36 and 67%. 10,11 Comparatively, this study had no in hospital deaths for the 15 patients with cirrhosis and only a 7.1% mortality rate at 1-year.…”
Section: Echocardiographic Findingsmentioning
confidence: 99%
“…1) With the increasing experience in the use of TAVI procedure and innovative devices, the incidence of complications has seen a steady decline. [2][3][4] Nevertheless, post-TAVI permanent pacemaker (PPM) implantation according to complete atrioventricular block (CAVB) remains a major complication. 5,6) The PPM implantation rate has been reported to vary from 2 to 51% according to various studies.…”
mentioning
confidence: 99%
“…he effectiveness of transcatheter aortic valve implantation (TAVI) for high-risk patients with severe symptomatic aortic stenosis has been clearly established. [1][2][3] The mortality rate and other outcomes associated with TAVI have been shown to be non-inferior to those associated with surgical aortic valve replacement. 4) Recently, several reports have shown that using local anesthesia with conscious sedation (LACS) during TAVI procedures decreases the procedure duration, length of stay in intensive care units (ICUs), and need for intraprocedural anesthesia-related medication support.…”
mentioning
confidence: 99%